Ecological impacts of invasive carp in Australian dryland rivers. Issue 11 (4th September 2019) - Marshall, Jonathan C.; Blessing, Joanna J.; Clifford, Sara E.; Hodges, Kate M.; Negus, Peter M.; Steward, Alisha L.
Abstract: Invasive carp are widely reported to harm ecosystems. In Australia, carp are a serious pest and, consequently, investigations of biocontrol options are under way. Best practice biocontrol requires cost/risk:benefit evaluation. To assist this, the impacts of carp on aquatic ecosystems have been summarized. To aid the evaluation of benefits, general predictions were tested by comparing dryland river ecosystems with and without carp, and ecosystem responses to a gradient in local carp density. Expectations were that in the presence of carp, and with increasing density, there would be increasing turbidity, decreasing densities of macrophytes and macroinvertebrates, and associated changes in assemblage composition, resulting in decreasing native fish density. Not all expected responses were found, indicating that the general understanding of carp impact requires modification for dryland rivers. Notably, carp did not increase turbidity or reduce macroinvertebrate density or composition, probably because of key attributes of dryland rivers. In contrast, there were large impacts on native fish biomass, not from the mechanisms expected, but from food resource monopolization by carp. Macrophyte occurrence was reduced, but macrophytes are naturally rare in these rivers. It is likely that the extirpation of an endangered river snail resulted from carp predation. Impacts on native fish may be reversible by carp control, but reversal of impacts on the snail may require carp elimination and snail reintroduction. Modelling is necessary to predict the probability of beneficial versus undesirable outcomes from carp control, and complementary measures to control other stressors may be needed. Benefits of carp control on dryland river ecosystems are fewer than generally predicted. This reinforces the point that ecological understanding cannot always be transferred between diverse settings and highlights the need to understand system characteristics relevant to causal impact pathways when applying generic carp impact models to specific settings. This has global relevance to future carp control efforts.